A Sialic Acid-Binding Protein SABP1 of Toxoplasma gondii Mediates Host Cell Attachment and Invasion - Xing, Mengen (J Infect Dis, 2020)
Many obligate intracellular apicomplexan parasites have adapted a distinct invasion mechanism involving a close interaction between the parasite ligands and the sialic acid (SA) receptor. We found that sialic acid binding protein-1 (SABP1), localized on the outer membrane of the zoonotic parasite Toxoplasma gondii, readily binds to sialic acid on the host cell surface. The binding was sensitive to neuraminidase treatment. Cells preincubated with recombinant SABP1 protein resisted parasite invasion in vitro. The parasite lost its invasion capacity and animal infectivity after the SABP1 gene was deleted, whereas complementation of the SABP1 gene restored the virulence of the knockout strain. These data establish the critical role of SABP1 in the invasion process of T. gondii. The previously uncharacterized protein, SABP1, facilitated T. gondii attachment and invasion via sialic acid receptors.